Fibrinogen Promotes Adhesion of Monocytic to Human Mesothelioma Cells - Shetty, Sreerama; Kumar, Anuradha; Pueblitz, Siegfried; Emri, Saleh; Gungen, Yucel; Johnson, Alice R; Idell, Steven (Thrombosis and Haemostasis, 1996)
Adhesion between monocytic and mesothelioma or pleural meso-thelial cells influences stromal remodeling in pleural neoplasia. We found that cultured monocytic cells (U937) adhere to either human pleural mesothelioma (MS-1) or mesothelial (MeT5A) cells in vitro. 125I-fibrinogen bound specifically and saturably to either cell line, and specific fibrinogen binding increased upon stimulation of these cells with proinflammatory agents such as phorbol myristate (PMA), lipo-polysaccharide (LPS) or tumor necrosis factor (TNF-±). We purified the fibrinogen receptor protein from a membrane fraction of MS-1 cells and identified it by immunoprecipitation as intercellular adhesion molecule (ICAM-1). Anti-ICAM-1 antibody or antisense oligonucleotides inhibited fibrinogen-mediated cell adhesion and binding of 125I-fibrinogen to mesothelioma or mesothelial cells. Cultured monocytic cells adhere to either mesothelioma or mesothelial cells, and the interaction is promoted by fibrinogen binding ICAM-1 at the cell surface. ICAM-1 is expressed by mesothelioma cells and CD 1 lb by macrophages in the fibrinous mesothelioma tumor stroma. The data suggest a common mechanism by which monocytic cells could adhere to either malignant mesothelioma cells or the mesothelial surface in pleural neoplasia.